Progression of IgM Monoclonal Gammopathy of Renal Significance (MGRS) to Symptomatic Waldenström Macroglobulinemia: A Case Report - Kenichi Ito; Hiroaki Shimoyamada; Kazuhiko Hirano; Naohiro Sekiguchi (Cancer Reports, 2025)
ABSTRACT Background Monoclonal gammopathy of renal significance (MGRS) is characterized as renal impairment caused by monoclonal protein but does not fulfill the criteria for specific hematologic malignancies. Most MGRS cases involve IgG, IgA, or light chains, but IgM‐MGRS remains poorly understood. Case We present a 74‐year‐old woman with IgM‐κ monoclonal proteinuria who initially declined further evaluation. Later, anemia was identified, and a systemic work‐up revealed monoclonal immunoglobulin deposition disease in the kidney and symptomatic Waldenström macroglobulinemia. Treatment with a Bruton's tyrosine kinase inhibitor, namely tirabrutinib, rapidly resolved both proteinuria and anemia. Conclusion This case highlights the importance of early renal biopsy and prompt intervention in suspected IgM‐MGRS.